Environmental and Genetic Variables Influencing Mitochondrial Health and Parkinson’s Disease Penetrance - Alessandra Zanon; Peter P. Pramstaller; Andrew A. Hicks; Irene Pichler (Parkinson's Disease)
There is strong evidence that impairment of mitochondrial function plays a key role in the pathogenesis of PD. The two key PD genes related to mitochondrial function are Parkin (PARK2) and PINK1 (PARK6), and also mutations in several other PD genes, including SNCA, LRRK2, DJ1, CHCHD2, and POLG, have been shown to induce mitochondrial stress. Many mutations are clearly pathogenic in some patients while carriers of other mutations either do not develop the disease or show a delayed onset, a phenomenon known as reduced penetrance. Indeed, for several mutations in autosomal dominant PD genes, penetrance is markedly reduced, whereas heterozygous carriers of recessive mutations may predispose to PD in a dominant manner, although with highly reduced penetrance, if additional disease modifiers are present. The identification and validation of such modifiers leading to reduced penetrance or increased susceptibility in the case of heterozygous carriers of recessive mutations are relevant for a better understanding of mechanisms contributing to disease onset. We discuss genetic and environmental factors as well as mitochondrial DNA alterations and protein-protein interactions, all involved in mitochondrial function, as potential causes to modify penetrance of mutations in dominant PD genes and to determine manifestation of heterozygous mutations in recessive PD genes.